Application of Blockchain Technology in Value Chain of Procurement in Manufacturing Enterprises - Wang, Yang; Men, Sichun; Guo, Tingting (Wireless Communications and Mobile Computing, 2021)
Blockchain technology, as a database which combines encryption algorithm, smart contract, consensus mechanism, time stamp, and other technologies, has received wide attention from all walks of life and can be used to solve such problems as asymmetric, incomplete, and untimely information in both interenterprise transactions and enterprise internal control management as a good solution owing to its characteristics of decentralization, traceability, and tamper-proofness. Consequently, it is worthy of studying how to apply blockchain technology to daily business activities of enterprises. In this paper, some problems existing in the value chain activities of the enterprise internal procurement are analyzed by designing the solutions to requisition, warehousing, and payment based on blockchain technology, in which the Hyperledger Fabric platform is selected as an implementation tool to simulate some purchasing data for testing procedures. After the successful test, the research conclusions and research prospects of this paper are thus proposed, proving the feasibility of applying the blockchain technology to the internal value chain management of the enterprise, which provides reference for the construction of the internal value chain management of the enterprise by the blockchain.